A+ guide to software managing, maintaining, and troubleshooting - Andrews, Jean 1946- (Course Technology/Cengage Learning, 2013)
Provides students with a comprehensive introduction to managing and maintaining computer software. This book integrates the Computing Technology Industry Association (CompTIA) A+ Exam objectives to prepare students for the software portions of the 220-801 and 220-802 certification exams.